STUDI PENYEBAB KECELAKAAN LALU LINTAS DI KOTA SURABAYA - Tahir, Anas (MEKTEK, 2006)
Surabaya City represent one of the biggest city in Indonesia with level of carownership is very high . Every year the amount of vehicle continue to increase so that can give impact to traffic jam , mussy and accident of traffic.From cause aspect accident of traffic in Surabaya city in generally caused by passenger vehicle which non public transport ( private car)and motorbike.Frequency accident of traffic in range of time 5 the last year ( 1998-2002) is counted 169 accident case with amount of victim counted 192 soul. Amount of soul victim pass away counted 29 people (15,10%), hardly injured 76 people ( 39,58%) and lightly injured 87 people ( 45,31%) the root cause accident is motorbike 48,10% and car 33,38%.Component of traffic type which often involve accident is motorbike driver with road street defector. The other cause is motorbike with car. The time of the biggest traffic accident is happened at 10.00 - 14.00 WIB.